Article Review: The Role of Blood-sucking Insect Vectors in the Spread of Jembrana Disease in Bali Cattle - Sukoco, Hendro; Irfan, Muhammad; Agustina, Agustina; Marsudi, Marsudi; Susanti S, Irma; Cahyani, Annisa Putri; Wahyuni, Sri; Siswanto, Ferbian Milas (Jurnal Peternakan, 2024)
ABSTRACT.  Jembrana disease is a contagious disease in cattle and causes enormous economic losses for farmers. This disease, known as bovine lentivirus, was first reported in 1964 in Jembrana District. Jembrana disease specifically attacks Bali cattle at various ages. The cause of this disease is a lentivirus from the Retoviridae family. Jembrana disease transmission occurs by direct contact and is mediated by blood-sucking insect vectors. Not all blood-sucking insects can be vectors for Jembrana disease. Some blood-sucking insects capable of spreading Jembrana disease are Tabanus rubidus flies Culicoides sp mosquitoes, and Aedes lineatopennis, which act as mechanical vectors. As for the Boophilus microplus tick, it is suspected that it acts as a biological vector. Even after re-testing the tick, it could not prove its role as a biological vector for JDV. Prevention and control of this disease can be carried out by vaccination, biosecurity, biosafety, administration of vitamins, isolation of infected livestock, and control of blood-sucking insect vectors by administering insecticides to cages.